MONOCYTOSIS AND HELICOBACTER PYLORI INFECTION: A CLINICAL AND PATHOPHYSIOLOGICAL REVIEW - Sebastian Musialik; Maciej Gołębski; Wojciech Nowak; Jagoda Mikołajczyk; Zuzanna Kukla; Stella Mieruszyńska; Paulina Krzemińska; Mirosław Sawicki; Izabela Sadowska; Jakub Włosiański (International Journal of Innovative Technologies in Social Science, 2025)
Background: Monocytosis (monocyte count >0.8–1.0 x 10⁹/L) signals chronic inflammation or infection. Helicobacter pylori (H. pylori), a widespread gastric pathogen causing chronic gastritis, has been linked to systemic inflammatory responses, including hematologic changes.Objective: This review examines clinical and pathophysiological evidence linking H. pylori infection to monocytosis, focusing on mechanisms and clinical implications.Key Findings:• Clinical Association: Numerous studies show H. pylori-infected individuals have elevated monocyte counts. Eradication therapy reduces these counts, suggesting a causal relationship.• Pathophysiology: H. pylori induces chronic gastric inflammation and systemic cytokine release (IL-6, TNF-α, IL-1β), along with bacterial products (HP-NAP, urease), stimulating bone marrow monocyte production and systemic low-grade inflammation.• Clinical Relevance: Monocytosis in H. pylori is often mild (≤2.0 x 10⁹/L) and reversible after eradication. It may aid diagnosis in endemic regions, especially in patients with dyspepsia or unexplained inflammation, after ruling out other causes.• Systemic Impact: This link illustrates H. pylori's broader inflammatory role beyond gastritis. It may contribute to conditions like immune thrombocytopenia (ITP) or metabolic syndrome.Conclusions: Monocytosis is a recognized hematologic feature of H. pylori infection, driven by immune activation and bone marrow stimulation. Though non-specific, it highlights the systemic effects of H. pylori. In high-prevalence areas, clinicians should consider H. pylori in cases of unexplained monocytosis. Post-eradication monocyte normalization may serve as a biomarker of inflammation resolution. Further studies should explore monocyte subsets and their utility in clinical practice.